Kidney Delayed Graft Function in Simultaneous Pancreas-Kidney Transplant Recipients Is Associated With Inferior Outcomes - Sofia Nehring Firmino, MS; Ekaterina Fedorova, MD; Eman A. Alshaikh, MBBS; Dixon Kaufman, MD, PhD; Jon Odorico, MD; Didier Mandelbrot, MD; Brad C. Astor, PhD; Sandesh Parajuli, MD (Transplantation Direct)
Background. Kidney delayed graft function (K-DGF) is associated with worse outcomes in simultaneous pancreas-kidney (SPK) recipients. However, its potential association with specific infections, rejection, and early complications remains unclear. Methods. We compared recipients with K-DGF to those without K-DGF among all adult SPK recipients transplanted at our center between January 2000 and December 2022 who had >2 wk of pancreas graft survival. Outcomes of interest included common posttransplant infections, including urinary tract infection (UTI), pneumonia, cytomegalovirus, BK, surgical wound infection, infected intra-abdominal fluid collection, graft rejection, and death-censored graft failure (DCGF) within the first year of transplant. We also looked for the need for early laparotomy within 90 d. Results. Seven hundred sixty-five SPK recipients were included, of whom 85 (11.1%) developed K-DGF. In Cox regression analysis, after adjustment for multiple key variables, K-DGF was associated/related with increased risk for UTI (adjusted hazard ratio [aHR], 1.76; 95% confidence interval [CI], 1.06-0.94; P = 0.03), infected intra-abdominal fluid collection (aHR, 2.14; 95% CI, 1.13-4.04; P = 0.02), and need for relaparotomy within 90 d (aHR, 2.07; 95% CI, 1.27-3.37; P = 0.003). K-DGF was also associated with increased risk for pancreas DCGF (aHR, 4.88; 95% CI, 1.90-12.51; P < 0.001). K-DGF was not associated with risk for other common infections of interest or graft rejection. Conclusions. K-DGF among SPK recipients is associated with an increased risk of UTI, infected intra-abdominal fluid collection, and the need for early relaparotomy, along with pancreas DCGF. Close monitoring and appropriate management are warranted in this higher-risk patient population.